The role of beliefs in entering and exiting the Bitcoin market - Daniela Balutel; Christopher Henry; Jorge Vásquez; Marcel-Christian Voia (Bank of Canada, 2024)
Cryptoassets, such as Bitcoin, represent a new type of financial technology that has grown substantially in recent years in terms of market size. Previous research has documented the characteristics and motivations of early Bitcoin adopters, but less work has been done studying those who choose to exit the Bitcoin market. We develop a theoretical model of both entry and exit to the Bitcoin market, the dynamics of which are driven by agents' beliefs about Bitcoin's survival. We connect the model to micro-level data from Canada, allowing us to empirically test the role of beliefs in transitioning to past ownership. Using a control function approach with appropriate exclusion restrictions, we estimate the effects of beliefs while controlling both for selection into or out of Bitcoin ownership and for possible simultaneity. We find evidence that beliefs are significant predictors of exit, while the size and direction of these effects differ across time and ownership status.
Keywords: D83; O33; E41; 330; Bank notes; Digital currencies and fintech; Econometric and statistical methods